Epidemiology, species distribution, clinical characteristics and mortality of candidaemia in a tertiary care university hospital in Turkey, 2007‐2014. Issue 7 (24th March 2017) - Yeşilkaya, Ayşegül; Azap, Özlem; Aydın, Mehtap; Akçil Ok, Mehtap
Summary: Candidaemia still continues to be a serious medical concern and the epidemiology of candidaemia varies according to geographical areas. We aim to determine the incidence, local epidemiology, Candida species distribution and crude mortality rates of candidaemia. We retrospectively evaluated candidaemia episodes in between January 2007 and August 2014. We compared demographic, clinical, microbiological findings and mortality rates of episodes caused by Candida albicans and non‐ albicans Candida species. Overall the candidaemia incidences were 1.23 episodes/1000 admissions. A significant negative slope among candidaemia episodes and years was determined. Overall C. albicans (54.6%) was the most common species followed by Candida glabrata, Candida tropicalis and Candida parapsilosis respectively. Preinfection hospital stay and length of hospital stay were statistically longer in patients with non‐ albicans Candida candidaemia than in patients with C. albicans candidaemia. The source of candidaemia was unknown in 52.5% of all episodes. Central venous catheters among non‐ albicans Candida candidaemia episodes and urinary system among C. albicans candidaemia episodes were common source of candidaemia compared to each other. Previous antifungal therapy preceding candidaemia and concomitant bacteraemia were significantly associated with non‐ albicans Candida candidaemia. Continuous local surveillance will preserve its pivotal importance in formulating empirical antifungal therapy and improving management of candidaemia.